virtus 3 years ago Why is (a+b)^n+1 =(a+b)^n(a+b) =a(a+b)^n +b(a+b)^n

1. hartnn

its the property: \(x^{n+1}=x*x^n\) then distributive property is used p(q+r)=pq+pr ok?

2. Fall12-13

It's a formula.

3. virtus

i don't get why (a+B)^n = a(a+b)^n +b(a+b)^n

4. Fall12-13

Just give us the question xD I mean, if there is one.

5. virtus

*(a+b)^n x (a+b)

6. ganeshie8

p(q+r)=pq+pr

7. ganeshie8

say p = (a+b)^n

8. hartnn

(a+b)^n = a(a+b)^n +b(a+b)^n<----not true (a+b)^n+1 = a(a+b)^n +b(a+b)^n<---true

9. virtus

(a+b)^n x (a+b) =a(a+b)^n +b(a+b)^n

10. virtus

i don't get why that is

11. ganeshie8

you want proof of distrubution property ?

12. virtus

ok

13. ganeshie8

no its okay.... ..u didnt get why distribution prperty works is it ?

14. virtus

yes

15. ganeshie8

basically you wanto understand why 2(3+4) = 2*3 + 2*4

16. Fall12-13

LOL

17. virtus

LOL that sounds pretty cool the way you put it

18. ganeshie8

idk the proof id love to see @TuringTest @KingGeorge @mukushla explain it

19. ganeshie8

well let me try

20. ganeshie8

2*100 = 100 + 100 right ?